SARS-CoV-2-Associated Multisystem Inflammatory Syndrome in a Child in Uganda: A Paediatric Experience in a Resource-Limited Setting - Thereza Piloya; Lydia Nakiyingi; Ivan Kimuli; James Kayima; Joseph Lubega; John Sekabira; Hellen T. Aanyu (Case Reports in Infectious Diseases)
SARS-CoV-2-associated Multisystem Inflammatory Syndrome in children (MIS-C) has been described in developed settings that have reported a high burden of COVID-19 cases. However, to date, there are few published cases of MIS-C that have been described in the African region. MIS-C has high morbidity and even mortality without a prompt diagnosis. We report a case of a 9-year-old girl who presented with typical clinical features of MIS-C in Uganda but had a delay in diagnosis. This case report aims to raise awareness among health providers in similar settings to improve clinical suspicion of MIS-C, facilitate prompt diagnosis and treatment, and thus improve outcomes.